2017
DOI: 10.2116/analsci.33.79
|View full text |Cite
|
Sign up to set email alerts
|

Structural Discrimination between Aβ(1–40) and Aβ(1–42) Peptides in Films with Vibrational Circular Dichroism Spectroscopy

Abstract: The secondary structure of full-length Aβ(1-40) and Aβ(1-42) peptides in films has been investigated with IR and vibrational circular dichroism (VCD) spectroscopy. From IR spectra, it is shown that the prepared films of Aβ(1-40) and Aβ(1-42) mainly comprise the β-sheet conformation that is characteristic of aggregated and fibrous Aβ. In the VCD spectra, the Aβ(1-42) film shows an intense and sharp band with left-handed optical activity at around 1625 cm -1 , while the Aβ(1-40) film shows a weak and broad band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The first reports of this phenomenon came from VCD studies using insulin resulting from a collaboration of the Nafie, Dukor, and Lednev laboratories. ,, They assigned a five feature VCD pattern in the overall amide I and II region to be indicative of fibril formation. Subsequent studies showed the phenomenon to be characteristic of a number of proteins and amyloidogenic peptides, which were induced to form fibrillar macro-structures, typically by dissolving the proteins in low pH media and heating under controlled conditions. ,,, , All the model systems studied so far have local conformations dominated by β-sheet secondary structures, as determined from the dominant IR bands. However, their electron microscopy (EM) morphologies varied as did VCD patterns, which could change, dependent on preparation protocols, even for the same protein, both in terms of the detailed bands and the overall sign patterns.…”
Section: Empirical Peptide Voa Studies Correlation Of Spectra With Se...mentioning
confidence: 99%
“…The first reports of this phenomenon came from VCD studies using insulin resulting from a collaboration of the Nafie, Dukor, and Lednev laboratories. ,, They assigned a five feature VCD pattern in the overall amide I and II region to be indicative of fibril formation. Subsequent studies showed the phenomenon to be characteristic of a number of proteins and amyloidogenic peptides, which were induced to form fibrillar macro-structures, typically by dissolving the proteins in low pH media and heating under controlled conditions. ,,, , All the model systems studied so far have local conformations dominated by β-sheet secondary structures, as determined from the dominant IR bands. However, their electron microscopy (EM) morphologies varied as did VCD patterns, which could change, dependent on preparation protocols, even for the same protein, both in terms of the detailed bands and the overall sign patterns.…”
Section: Empirical Peptide Voa Studies Correlation Of Spectra With Se...mentioning
confidence: 99%
“…Circular dichroism (CD) is a representative analytical technique for the configurational and conformational study of optically active compounds, particularly peptides and proteins. [3][4][5][6] For precise CD studies, calibrating a CD spectrometer with proper accuracy of absorbance scale and the linearity is important, 7 and research into calibration methods for CD spectrometers has been carried out. The compendial procedures for CD spectrometers were defined in the 4th European Pharmacopoeia (EP) for the development of drugs in 2002.…”
Section: Introductionmentioning
confidence: 99%